(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Emotional intelligence as the capacity to interpret, access and produce emotions, as well as supporting our thinking, knowing emotions and emotional awareness, and controlling emotions reflectively in order to foster emotional and intellectual development. We will learn our self-better by strengthening our EI, and then we will understand more about the other. Besides that, under some situations, we should change our conduct. We should do our hardest to mitigate the harmful protection function by recognizing our capacity to change EI, which can have a poor effect on ourselves and situation around us. Once we recognize our feelings, we will act and react based on our perception and show the result that will determine how to behave and that will involve the defensive mechanism. The intellect one of amplifies thoughts by giving an unconscious and aware triggering evaluation that is more comprehensive and intensive. Physiological signals of a particular feeling. This study proposed to determine the combination assessment and Bar-On to establish emotional intelligence modelling instrument and observe the interaction between emotional intelligence and processes of psychological security. We will then figure out how relevant the EQ is by utilizing this literature review and how it will have a positive influence on ourselves and others.